Conceptions and practices of metadata quality for frbr user tasks resources discovery in institutional repositories - Sarif Abdullah, Sharifah Nur Amirah; Othman, Roslina (IIUM Press, International Islamic University Malaysia, 2017)
The study applied a Metadata Quality Framework using three metrics, namely accuracy, consistency and completeness; and FRBR User Tasks Conceptual Model. The objectives of the study are to examine the current standard of metadata creation practices in institutional repositories, to examine metadata quality errors in institutional repositories, to investigate the perceived agreement of metadata quality and metadata quality errors among institutional repository staff, and to identify the relationship between metadata quality and FRBR user tasks